Research on the Preparation of Modified TiO2 Composite Coatings with Anti-Fouling and Flashover Resistance - ZHANG Jie, ZOU Junwen, LIU Xueguang, LI Xiaoying (Cailiao Baohu)
In order to effectively reduce the occurrence of pollution flashover accidents caused by surface contamination of transmission line insulators， a new fluorocarbon coating material was prepared by combining modified nano-TiO2， PTFE and fluorocarbon resin FEVE using compressed air spraying technology.The optimum addition amount of modified TiO2 particles was discussed.The microstructure was studied using scanning electron microscopy (SEM) and atomic force microscopy (AFM).The hydrophobicity， self-cleaning properties and anti-ultraviolet aging resistance were analyzed using a contact angle measurement instrument.The results showed that the optimum addition amount of modified nano-TiO2 was 4%，the adhesion of the coating reached grade 0，and the maximum static contact angle was 121°.The surface of the anti-pollution flashover composite coating prepared with modified TiO2 exhibited numerous micro-nano scale columnar cone tip structures， resulting in higher roughness.Its hydrophobicity， self-cleaning ability， and anti-ultraviolet aging resistance were improved， demonstrating excellent antipollution flashover performance.